Service providers endorse integrated services model for youth with mental health and substance use challenges: findings from a discrete choice experiment - Lisa D. Hawke; Lehana Thabane; Srividya N. Iyer; Alexia Jaouich; Paula Reaume-Zimmer; Joanna Henderson (BMC, 2021)
Abstract Background Given high rates of mental health and substance challenges among youth and substantial system access barriers, system innovation is required. Integrated youth services (IYS) models aim to transform youth mental health and substance use services by creating integrative, collaborative models of care in youth-friendly settings. This study examines service provider perspectives on the key service components to include in IYS models. Method A discrete choice experiment modeled service provider preferences for the service components of IYSs. The sample includes 388 service provider/agency leader participants (age 18+) from youth-serving organizations in Ontario. Importance scores and utility values were calculated for 12 attributes represented by four levels each. Latent class analysis identified subgroups of participants with different preferences. Results The majority of participants were direct service providers working in larger organizations in the mental health and/or substance use sectors in large urban centers. Participants strongly endorsed service models that provide rapid access to the widest variety of culturally sensitive service options, with supplementary e-health services, in youth-focused community settings with evening and weekend hours. They prefer caregiver involvement in youth services and treatment decisions and support youth and family engagement. Latent class analyses reveal three segments of service providers: a Youth-Focused Service Accessibility segment representing 62.1% (241/388) of participants, a Service Options segment representing 27.6% (107/388) of participants, and a Caregiver Integration segment representing 10.3% (40/388) of participants. Within these segments, the degree of prioritization of the various service components differ; however, the overall endorsement of the service components remains largely consistent across classes for most attributes. The segments did not differ based on demographic or agency characteristics. Conclusions The core characteristics of IYS settings for youth with mental health and substance use challenges, i.e., rapid access to a wide range of youth-oriented services, are strong priorities of service providers and youth-serving agency leaders. These findings confirm that youth-oriented service providers endorse the importance and relevance of IYS models as a whole; strong service provider buy-in to the model is expected to facilitate development, implementation and scaling of IYS models. Hearing stakeholder perspectives, including those of service providers, youth, and caregivers, is essential to developing, effectively implementing, and scaling effective youth services.